Structure and properties of some chiralanes and chirolanes. (18th June 2018) - Novak, Igor
ABSTRACT: The molecular structures, spectra and properties of six chiralanes and chirolanes (approximately spheroidal, saturated, cage hydrocarbons) have been determined by density functional theory (DFT) quantum chemistry calculations. The main features determined are: molecular geometry, partial atomic charges, standard enthalpy of formation, IR, nuclear magnetic resonance (NMR) and circular dichroism (CD) spectra. On the basis of the calculated standard enthalpies of formation and highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) gaps, we suggest that chiralanes/chirolanes are potential synthetic targets. We have calculated the anomalously large downfield 13 C-NMR shifts for endohedral carbons in the spectra of [5.5] and [5.7]chiralanes. Abstract :